An evaluation of the differences in the composition of humic acids in soils under oak and pine forest by GC-MS after mild degradation - González-Vila, F L; Almendros, G; Martin, F (Plant and soil, 1987)
Significant differences were found in the products released after eight samples of humic acids (HA's) isolated from soils under mediterranean pine and oak forests underwent mild degradation. A number of compounds, including typical degradation products of lignins, were found exclusively in the HA's from the soils under pine forests. The aliphatic constituents were more firmly retained in the HA's under oak, which presented mean values for aromatic acids lower than the humic samples from pine forests. Different types of diterpene resin acids were also found amongst the mild degradation products of HA's from the studied areas.
Keywords: Forest soils; humic acids; Lipids; mild degradation; Pinus; Quercus; resin acids